Second victim support structures in anaesthesia: a cross-sectional survey in Belgian anaesthesiologists. (24th March 2021) - Nijs, Kristof; Seys, Deborah; Coppens, Steve; Van De Velde, Marc; Vanhaecht, Kris
Abstract: Background: Anaesthesiologists are prone to patient safety situations after which second victim symptoms can occur. In international literature, a majority of these second victims indicated that they were emotionally affected in the aftermath of a patient safety incident (PSI) and received little institutional support after these events. Objective: To study the current second victim support structures in anaesthesia departments in Belgium. Methods: An observational cross-sectional survey. Belgian anaesthesiologists and anaesthesiologists in training were contacted through e-mail from May 27th until 15 July 2020. Results: In total, 456 participants completed the online survey. 73.7% ( n = 336) of the participants encountered a PSI during the last year of their medical practice. 80.9% ( n = 368) of respondents answered that they do discuss incidents with their colleagues. 18.0% ( n = 82) discussed all incidents. 19.3% ( n = 88) admitted that these incidents are never discussed in their department. 15.4% of participants ( n = 70) experienced or thought that the culture is negative during these PSI discussions. 17.3% ( n = 79) scored the culture neutral. Anaesthesiologists who encountered a PSI in the last years scored the support of their anaesthesia department a mean score of 1.59 (ranging from −10 to +10). A significant correlation ( P < 0.05) was found between the culture during the morbidity and mortality meetings, the support after the incidents and the perceived quality of the anaesthesia department. Conclusion: Of the participating anaesthesiologist in Belgium, 80.9% discussed some PSIs and 18.0% discussed all PSIs as a normal part of their staff functioning with an experienced positive or neutral culture during these meetings in 84.6%. Psychological safety within the anaesthesiology departments is globally good; however, it could and should be optimized. This optimization process warrants further investigations in the future.